Verbal Clauses in the Lamaholot Language, Lewoawan Dialect: A Morphosyntactic-Typological Study - Philipus Wai Lawet; Bartoldus Sora Leba (Universitas Muhammadiyah Enrekang, 2025)
This research examines verb change process, verb clause’s basic structure, and the typology aspects of BLDL verbal clauses as part of the Morphosyntactic Typology study. The data of this qualitative descriptive research comes from daily conversations of the Lewoawan village community. Data collection techniques include free-involved listening-speaking, recording and taking notes. The data were analyzed by reducing, presenting and drawing conclusions. The results show that (1) syntactically BLDL verbs consist of intransitive and transitive verbs, (2) morphologically BLDL incomplete verbs require the attachment of clitics and verb markers that are adjusted to the sentence’s subject pronoun, (3) the basic structures of BLDL verbal clauses are intransitive, mono-transitive and ditransitive, (4) the typology of word order in BLDL verb clauses is SV in intransitive, SVO in mono-transitive and SVOO in ditransitive, (5) grammatically typologically BLDL is an Active Language, namely treating A the same as S and the same as P.